PEMBERDAYAAN PEREKONOMIAN KELOMPOK PETANI LELE MELALUI PROGRAM “PAMAN LELE JEPRET” DI DESA MANARUWI, BANGIL, PASURUAN - M Daimul Abror (LPPM Universitas Yudharta Pasuruan, 2018)
Manauwi Village is one of the villages in district of Bangil, Pasuruan Regency. Manaruwi village has good potential in the field of freshwater fisheries, especially catfish. In order to empower rural communities in the field of fisheries, community assistance was carried out in the "PAMAN LELE JEPRET" program, namely the empowerment of catfish farmers by providing training in making alternative catfish feed from basic fish waste materials. The objective of the mentoring program is to develop innovations in the manufacture of economical alternative catfish feed through assistance in activities: (1) dissemination of production of alternative catfish feeds, (2) Assistance in the production of catfish feed from snap fish, (3) Assistance of catfish cultivation with alternative catfish feeding, and (4) assistance with packing products that are suitable for sale. The result of the mentoring program is that the community succeeded in producing alternative catfish feed from snap fish with economical production costs without reducing the catfish weight compared to the manufacturer's catfish feed. Mentoring activities have also increased the knowledge of group members in their efforts to produce these alternative feeds widely with marketable packing, so as to provide higher income for kele farmer groups in manaruwi village